Pengaruh Green Brand dan Green Trust Terhadap Keputusan Pembelian Produk The Body Shop - Yasri, Yasri; Engriani, Yunita; Rahmi, Maulina (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2017)
The purpose of this study is to analyze: (1) The influence of green brand on green trust, (2) The influence of green brand on purchase decision (3) The influence of green trust on purchase decision. This type of research is causative research. The population of this study are consumers who visited The Body Shop shop in Padang City. The sampling technique of this research is non probability sampling technique with accidental sampling method with total sample amounted to 100 people. The data used are primary data and secondary data. Data analysis technique used is path analysis. Hypothesis test in this research is done by t test. The result of the research showed: (1) Green brand significant and positive to green trust with value of acceptance 0.815 (2) Green brand significant and positive to purchase decision with value of acceptance 0,545 (3) Green trust significant and positive to purchase decision with value of acceptance 0,434. Â Keywords: Green Brand, Green Trust, Purchase Decision